A New Approach to HCI in Technical Education: Creating Mobile Communication Tools with the User in Mind - Omar, Nurul Ihsaniah; Ahmad, Azura (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The increasing impact of human-computer interaction has created new chances to assist learners traversing intricate and technical educational pathways. Despite the swift advancement of digital technology and the growing accessibility of specialized professions, several students encounter difficulties in completely engaging due to communication obstacles. A primary obstacle is the lack of organized, accessible vocabulary relevant to their disciplines, which impedes their capacity to interact with resources and articulate concepts proficiently. This study investigates the essential components necessary for creating a mobile platform that assists learners in overcoming communication barriers in technical and scientific fields. The research underscores the significance of connecting digital solutions with the genuine requirements and preferences of learners, prioritizing user experience and interface design. The results offer valuable insights for developers, educators, and content creators aiming to design interactive technologies that are both accessible and effective. Focusing on the user during the design process helps maximize human-computer interaction, hence improving understanding, involvement, and sustained engagement in specialized domains.